Sex steroid hormones in relation to Barrett's esophagus: an analysis of the FINBAR Study. (27th February 2017) - Cook, M. B.; Wood, S.; Hyland, P. L.; Caron, P.; Drahos, J.; Falk, R. T.; Pfeiffer, R. M.; Dawsey, S. M.; Abnet, C. C.; Taylor, P. R.; Guillemette, C.; Murray, L. J.; et al.
Summary: Previously, we observed strong positive associations between circulating concentrations of free testosterone and free dihydrotestosterone (DHT) in relation to Barrett's esophagus in a US male military population. To replicate these findings, we conducted a second study of sex steroid hormones and Barrett's esophagus in the Factors Influencing the Barrett/Adenocarcinoma Relationship (FINBAR) Study based in Northern Ireland and Ireland. We used mass spectrometry to quantitate EDTA plasma concentrations of nine sex steroid hormones and ELISA to quantitate sex hormone‐binding globulin in 177 male Barrett's esophagus cases and 185 male general population controls within the FINBAR Study. Free testosterone, free DHT, and free estradiol were estimated using standard formulas. Multivariable logistic regression estimated odds ratios (OR) and 95% confidence intervals (95%CI) of associations between exposures and Barrett's esophagus. While plasma hormone and sex hormone‐binding globulin concentrations were not associated with all cases of Barrett's esophagus, we did observe positive associations with estrogens in younger men (e.g. estrone + estradiol ORcontinuous per ½ IQR = 2.92, 95%CI:1.08, 7.89), and free androgens in men with higher waist‐to‐hip ratios (e.g. free testosterone ORcontinuous per ½ IQR = 2.71, 95%CI:1.06, 6.92). Stratification by body mass index, antireflux medications, and geographic location did not materially affect the results. This study found evidence for associations between circulating sex steroid hormones and Barrett's esophagus in younger men and men with higher waist‐to‐hip ratios. Further studies are necessary to elucidate whether sex steroid hormones are consistently associated with esophageal adenocarcinogenesis.